Tissue Proteinase Activity in Indian Mackerel (Rastrelliger kanagurta) during Iced Storage - M.R., Raghunath; Jose, Leema (Fishery Technology, 2025)
Tissue proteinase activity (TPA) during iced storage of mackerel (Rastrelliger kanagurta) and its effect on tissue proteins were followed by assay of proteinase activity and SDS-PAGE of tissue homogenates, respectively. TPA in mackerel is predominantly expressed at pH 3, 4, 9 and 10. The activities at pH 3 and 4 were initially higher than that at alkaline pH. TPA at the acid pH range were observed to decrease during iced storage and were always at lower than original levels, although there was a transient increase at 4-6 days of iced storage. TPA in the alkaline pH range (9 and 10) remained mostly unaffected till 6-8 days of iced storage after which, a slight decrease was observed. However, at both pH ranges, the activity increased sharply after 11 days, owing to diffusion of visceral/microbial proteinases from the belly cavity due to spoilage. Electropherogram of the muscle homogenates revealed early breakdown of high molecular weight proteins followed by lower molecular weight proteins.